Opportunistic fusion of ranges from different sources for indoor positioning - Álvarez-Merino, Carlos Simón; Luo Chen, Hao Qiang; Khatib, Emil Jatib; Barco-Moreno, Raquel (Institute of Electrical and Electronics Engineers, 2021)
Ultra-Wide Band (UWB) technology stands out as one of the most promising technologies for locating the user in indoor scenarios for the new 5G mobile generation. As a drawback, it requires a dense infrastructure. For this study, a simulation of a real environment with UWB and Long Term Evolution (LTE) base stations for positioning users is presented, tracked by an Extended Kalman Filter (EKF). The proposed method uses information that is unusable with UWB alone, and combines it with LTE location, improving the precision for the latter and enabling sparse infrastructure deployments.
Keywords: Telecomunicaciones; Location; UWB; Position control; Location fusion; Indoor positioning; Mobile network